Positive psychology in the learning and teaching of older adults - Niewczas, Sylwia (Activation-innovation-inspiration in (glotto) didactics, 2022)
The aim of the paper is to present the current state of research in the field of positive psychology and its applications to teaching/ learning languages to older adults. For many years, cognitive perspective had dominated research in applied linguistics. In recent years, however, a growing popularity of positive psychology and focus on positive emotions can be observed. In the first part of the paper, the introduction of positive psychology to education and language teaching will be described including Seligman’s PERMA and Oxford’s EMPHATICS models. In is model, Seligman hypothesized that 5 elements account for a general wellbeing: positive emotions (P), engagement (E), developing positive interpersonal relationship (R), finding meaning (M) and recognizing areas of accomplishment and achievement (A). The paper distinguishes between the two periods: the early period started by MacIntyre and Gregersen (2012-2015) and the current period which started in 2016 (the flourishing of positive psychology in education). Positive psychology research will be presented as well and possible implications of positive psychology in teaching of older adults.